2020
DOI: 10.1051/e3sconf/202016404032
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing factors of urban renovation

Abstract: To optimize the organizational and technological model of construction of buildings and structures in a dense urban environment, it is necessary to take into account the factors that have a destabilizing effect on the process of construction and installation works, and arising from the very definition of " constrained urban development", which involves getting near buildings, structures and linearly extended objects in the zone of influence of new construction or reconstruction. This article highlights a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…(2018) and others analyzed the negative factors and optimization of the organizational and technological model of the construction of buildings and structures in conditions of dense urban development. The study showed that it is possible to create a single global model for assessing the degree of construction complexity of the object being built, taking into account external destabilizing factors of the existing infrastructure on the construction site [38].…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2018) and others analyzed the negative factors and optimization of the organizational and technological model of the construction of buildings and structures in conditions of dense urban development. The study showed that it is possible to create a single global model for assessing the degree of construction complexity of the object being built, taking into account external destabilizing factors of the existing infrastructure on the construction site [38].…”
Section: Literature Reviewmentioning
confidence: 99%